Delivery and evaluation of a food science professional development training for Mississippi career technical education teachers. Issue 4 (15th August 2021) - Hendrix, Jasmine D.; Campbell, Yan L.; Zhang, Xue; Downey, Laura H.; Jagger, Carla B.; Schilling, M. Wes
Abstract: Professional development for Career Technical Education (CTE) is needed to effectively implement food science curricula in secondary education courses. Providing CTE teachers with professional development training supports increased awareness of food science academic and career pathways among students. The goal of this study was to assess a food science professional development training for Mississippi CTE teachers that would increase their self‐perceived knowledge, self‐perceived ability to conduct specific food science skills, and self‐efficacy to implement food science‐based instruction. Thirty‐one teachers participated in the 2‐h professional development training that provided teachers an experiential learning opportunity to learn and apply food science concepts. Results indicated that the food science professional development training was effective at increasing teachers' self‐perceived knowledge and ability to conduct food science skills since the average scores (five‐point Likert‐type scale, n  = 28) in all statements increased ( p  < 0.001) post training. For example, teachers self‐perceived knowledge of the five D's of food product development at pre‐survey ( M  = 2.00 ± 0.94) increased ( p  < 0.001) after the training ( M  = 4.29 ± 0.60). In addition, teachers' self‐perceived ability to employ the five D's of food product development before the training ( M  = 0.31 ± 0.54, three‐point scale) significantly increased ( p  < 0.05) post training ( M  = 1.72 ± 0.53). Post training, more than 77% of the teachers "agreed" or "strongly agreed" to six out of nine self‐efficacy statements which affirmed their belief to teach food science concepts. Overall, teachers were satisfied with the food science professional development training.